Zmowa kobiet? Inscenizacje feministyczne w polskim teatrze dwudziestolecia międzywojennego - Diana Poskuta-Włodek (Przestrzenie Teorii)
The first wave of feminism in Poland consisted of a wide range of events. All women who were educated, independent, and professionally active and successful were regarded as feminists (regardless of their self-identification). Women of the theater, i.e., playwrights, directors, actresses and scenographers, who occupied themselves with “womanly subjects” in the 1920s and 1930s, created feminist theater which was important though it did not last long. In numerous feminist performances, theatrical productions dealt with subjects such as women in control of their own sexuality and bodies, women’s full participation in life, as well as economic independence and equal rights for women. Feminists in Polish theater, for example, Zofia Modrzewska, Maria Morozowicz-Szczepkowska, Irena Grywińska and Marcelina Grabowska, were typically not treated seriously by male critics, who were condescending, scornful, and unable to transcend their male perspective.